A green, accurate and sensitive analytical method based on vortex assisted deep eutectic solvent-liquid phase microextraction for the determination of cobalt by slotted quartz tube flame atomic absorption spectrometry - Tekin, Zeynep; Unutkan, Tugce; Erulas, Fatih; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2020)
Preconcentration of cobalt was carried out with deep eutectic solvent based liquid phase microextraction (DES-LPME) for trace determination by a slotted quartz tube (SQT) attached flame atomic absorption spectrometry (FAAS) system. Choline chloride and phenol in a 1:2 M ratio was used as a green solvent to extract cobalt from the aqueous sample solution. Key parameters influencing the extraction efficiency of cobalt were examined and optimized. Under the conditions optimized, the linear dynamic range was found between 5.0 and 50 mu g L-1, and the limits of detection and quantification (LOD and LOQ) were calculated as 2.0 and 6.6 mu g L-1, respectively. The detection power of the conventional FAAS was improved upon by 67 folds using the optimized DES-LPMESQT-FAAS method. The developed analytical method was successfully applied for the determination of cobalt in linden tea samples and the recovery results obtained for different spiked concentrations (20, 30 and 40 mu g L-1) were remarkable (approximate to 100%).
Keywords: Cobalt; Deep eutectic solvent; Liquid phase microextraction; Flame atomic absorption spectrometry; WATER SAMPLES; FOOD SAMPLES; EXTRACTION; NICKEL; COPPER; PRECONCENTRATION; CADMIUM; IONS; LEAD; FAAS; Chemistry; Food Science & Technology; Nutrition & Dietetics